Analisis Distribusi Temperatur Dengan Metode CFD Pada Fluida Primer Integral Pressurized Water Reactor (iPWR) - Putri, Sunny Ineza; 'Atifah, Nailul; Syawaludin, Adlisyah Hakim; Hutasoit, Leonardo Sintong Partogi (Jurnal Inovasi Ilmu Pengetahuan dan Teknologi (JIPTEK), 2024)
The fluid circulating in the iPWR uses two working fluids, the primary fluid as a reactor coolant which delivers heat to the secondary fluid to generate steam. The secondary working fluid flows in the steam generator pipe without direct contact with the primary working fluid. The cooling process of the primary working fluid can be simulated using the Computational Fluid Dynamics (CFD) method to obtain the temperature distribution in the reactor core. So, this research will focus on analyzing the temperature distribution of the first working fluid in the iPWR reactor core using the CFD method. Simulation of the primary fluid flow being heated or cooled under normal conditions to reach the upper and lower temperature targets by adjusting the fluid flow speed used. Under normal and/or mal function conditions, the water temperature does not reach saturation. However, this research has not considered the material condition and pressure when the auxiliary tools are disabled.